Desenvolvimento de Sistemas Orientados a Objetos Utilizando o Sistema Transformacional Draco-Puc - Bergmann, Ulf; Prado, Antonio Francisco do; Leite, Julio Cesar Sampaio do Prado (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24455, 1996)
Even not being an unanimity in Software Engineering, there is no way of denying the impact of Object Oriented Technology in all phases of the development process. Besides coming out many object oriented languages, many methods and techniques were born to support specification work and design of object oriented systems. This paper reports the building and how to use a support environment of object oriented development. The environment aggregates a graphical interface with the Draco-Puc machine transformational system. The environment characterizes itself by utilizing transformation technology that allows automatic C++ code generation from specifications of high level abstraction. The paper emphasizes Draco-Puc machine integration as well as its use for code generating. A real case based example is utilized to demonstrate the capacities and utilities of the proposed environment.